Chile’s 2021 constitutional neurorights amendment: a cognitive sovereignty preliminary conceptual framework for non-traditional security analysis - Karolina Zhukoff (Frontiers in Public Health, 2026)
Chile’s 2021 constitutional amendment on neurorights, the first such provision anywhere in the world, is widely characterized in the literature as a rushed, conceptually underdeveloped instance of liberal rights extension. This article proposes an alternative framing. Examined through the intersecting lenses of non-traditional security (NTS) theory, international law, and the political history of post-colonial statehood and technological dependency, this article challenges this view and proposes that the 2021 constitutional amendment can be functionally interpreted as acquiring the structure of cognitive sovereignty , defined here as the state’s independent authority over the mental and identity-related domains of its population against disproportionate foreign neurotechnological influence. Three analytical dimensions support this functional reading. First, the amendment’s placement within Chile’s restrictive bioethical architecture, − which severely constrains bodily autonomy while constitutionally elevating neural governance, − is structurally inconsistent with a liberalizing rights logic and is more coherently read as an extension of conservative state authority over the cognitive domain. Second, Chile’s history of foreign intervention and the Pinochet regime’s systematic use of psychological methods to fracture political consciousness, constitutes a historical context within which the amendment acquires cognitive sovereignty significance, even if history did not directly motivate its drafters. Third, Chile’s structural position as a consumer rather than producer of neurotechnology, operating under the conditions of technological asymmetry, provides geopolitical context within which the amendment may function as a reverse regulatory signal toward technologically dominant actors, regardless of whether it was designed as such. Taken together, these three contextual dimensions challenge the dismissal of the amendment as conceptually underdeveloped and suggest that, when functionally interpreted through cognitive sovereignty lens, neurorights may acquire strategic significance as NTS instruments – a reading that complements rather than replaces the human-rights framing. The article concludes by exploring the conditions under which constitutional neurorights may be adopted by other technologically peripheral states as for cognitive sovereignty purposes, with implications for global neurogovernance.